A Decade of Research on Educational Investment in Human Capital: A Review and Bibliometric Perspective - Badrud Tamam; Aminudin Aminudin; Riema Afriani Kusumadewi; Cucun Sunaengsih; Fetty Poerwita Sary; Saprolla Rollie C. Deporos (Journal of Innovation in Educational and Cultural Research, 2026)
Driven by the growing urgency of digital disruption and the multifaceted challenges of sustainable development, this study explores the transformative landscape of human capital investment over the past decade. The study aimed to map global publication trends, geographic distribution, and thematic evolution in education investment from 2015 to 2025. It employed bibliometric and SLR methodologies based on Scopus data, using VOSviewer and Biblioshiny. The results show a significant surge in scholarly output, peaking in 2022, with China emerging as the dominant contributor to global discourse. Key findings highlight a critical thematic transition from traditional family sociology to high-impact contemporary issues, including digital innovation, the green economy, and AI-mediated labor markets. The study concludes that a radical curriculum reconstruction prioritizing digital literacy and technological adaptability is crucial for fostering national resilience. This research contributes to the field of educational management by providing a systematic framework for understanding how new technologies are redefining the economic value of human capital, offering policymakers strategic insights to foster inclusive, knowledge-based, and sustainable economic growth in the digital age.